2007
DOI: 10.1097/00000542-200702000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for the Occurrence of Electroencephalogram Abnormalities during Induction of Anesthesia with Sevoflurane in Nonepileptic Patients

Abstract: Induction with sevoflurane may result in epileptiform electroencephalographic activity. Only electroencephalographic monitoring allows the diagnosis. Risk factors are mainly female sex, short delay to onset of anesthesia, and high alveolar sevoflurane concentration. Induction with high sevoflurane concentration is controversial mainly in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
2
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 34 publications
3
45
2
2
Order By: Relevance
“…However, this is a dose-dependent phenomenon and typically observed at far higher concentrations than used in the current study. 41 …”
Section: Discussionmentioning
confidence: 99%
“…However, this is a dose-dependent phenomenon and typically observed at far higher concentrations than used in the current study. 41 …”
Section: Discussionmentioning
confidence: 99%
“…Based on the descriptions of Vakkuri et al [4], the following EEG patterns which were regarded as epileptiform patterns [2] were distinguished: DSP (delta with spikes; delta activity of any frequency with regular or irregular spikes), PSR (rhythmic polyspikes; waveform with more than two negative and positive deflections appearing at regular intervals, associated with slow wave or mixed frequency EEG activity between spike complexes), PED (periodic epileptiform discharges), SSP (suppression with spikes; short episodes consisting mostly of a single spike appearing during complete EEG suppression). Examples are presented in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Advantages of sevoflurane are that it is nonpungent and that it is characterized by a lack of upper airway irritation [1]. The use of high concentrations of 7–8% sevoflurane has been recommended to accelerate the loss of consciousness and to minimize the risk of body movements, agitation, breath holding, and coughing [2], [3]. The cardiac output is better maintained at deep anaesthesia levels compared with halothane [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epileptiform discharges were seen in 12 of 40 healthy adult patients who were randomly allocated to different modes of sevoflurane induction with risk factors identified as being a large expired concentration of sevoflurane, the speed of anesthetic induction and female sex. 8 Voss et al 9 report that epileptiform activity has been observed with numerous general anesthetic agents including enflurane, etomidate, sevoflurane and propofol. The true incidence and underlying mechanisms are largely unknown.…”
Section: Discussionmentioning
confidence: 99%